New euophryine jumping spiders from Papua New Guinea (Araneae: Salticidae: Euophryinae) - Zhang, Jun-Xia; Maddison, Wayne P. (Zootaxa, 2012)
Thirty-four new species and five new genera of euophryine jumping spiders from Papua New Guinea are described. Thenew genera are Chalcolemia (type species C. nakanai sp. nov.), Phasmolia (type species P. elegans sp. nov.), Variratina(type species V. minuta sp. nov.), Viribestus (type species V. suyanensis sp. nov.) and Zabkattus (type species Z. brevis sp.nov., plus new species Z. furcatus sp. nov., Z. richardsi sp. nov. and Z. trapeziformis sp. nov.). The other new species belong to the genera Bathippus (B. directus sp. nov., B. gahavisuka sp. nov., B. korei sp. nov., B. madang sp. nov.), Canama(C. extranea sp. nov., C. fimoi sp. nov., C. triramosa sp. nov.), Omoedus (O. brevis sp. nov., O. darleyorum sp. nov., O.meyeri sp. nov., O. omundseni sp. nov., O. papuanus sp. nov., O. swiftorum sp. nov., O. tortuosus sp. nov.), Paraharmochi-rus (P. tualapaensis sp. nov.), Sobasina (S. wanlessi sp. nov.), Thorelliola (T. aliena sp. nov., T. crebra sp. nov., T. joannaesp. nov., T. squamosa sp. nov., T. tamasi sp. nov., T. tualapa sp. nov., T. zabkai sp. nov.) and Xenocytaea (X. agnarssonisp. nov., X. albomaculata sp. nov., X. proszynskii sp. nov.). The genera Pystira and Zenodorus are both considered as juniorsynonyms of Omoedus because of their similar genital structure. Species of these two genera are therefore transferred toOmoedus. Diagnostic illustrations are provided for all new species, and photographs of living spiders are also provided when available.